Synergistic effect of thermoplastic phenolic resin and multiwalled carbon nanotubes on the crystallization of polyoxymethylene. Issue 7 (20th February 2020) - Xue, Meiling; Lv, Kanghui; Gao, Shengqiang; Lu, Xiangzhou; Liu, Yingjie; Yan, Shouke
Abstract: To reduce the crystallization rate of polyoxymethylene (POM) to meet the requirement of thick‐walled and large‐sized articles production, and maintain high crystallinity as well as obtain refined crystalline grains to ensure the strength and stiffness simultaneously, thermoplastic phenolic resin (PF) and multiwalled carbon nanotubes (MWCNTs) were used as crystal growth inhibitor and nucleating agent, respectively, and their effects on the crystallization of POM were studied in details. The results showed that PF is an effective inhibitor and MWCNTs exhibits excellent nucleation effect on POM. Based on the obtained results, their synergistic influences on the crystallization process of POM were investigated. It is found that the objective of decreasing the crystallization rate while maintaining high crystallinity and forming fine crystalline grains can be realized. The 97/3/1 wt% POM/PF/MWCNTs, compared with those of neat POM, The T c shifts by 3.3°C to a lower temperature, the crystallization enthalpy increases by 16.1 J/g and the full width at half‐maximum widens by 48.5%. The modulation effect of PF and MWCNTs on the crystallization is closely related to the PF content and dispersion, the distribution and dispersion of MWCNTs in the PF and POM phases. Abstract : The prominent crystallization characteristic of polyoxymethylene (POM) is its high crystallinity with coarse crystalline grains formed under a very fast crystallization rate, which restricts the direct molding of the thick‐walled and large‐sized parts as well as the rapid continuous processing of sheets/bars of its products. The synergistic effect of thermoplastic phenolic resin and multiwalled carbon nanotubes can reduce the crystallization rate of POM, while maintaining or increasing its crystallinity. Therefore, refined crystalline grains can be obtained.